Improved bactericidal capacity of UV-B radiation against E. coli strains by photosensitizing bacteria with fructosazine – An advanced Maillard reaction product. (15th January 2019) - Bhattacherjee, Abhishek; Hrynets, Yuliya; Betti, Mirko
Highlights: Fructosazine can emit fluorescent light but not as efficiently as tryptophan. Exposure to UV-B radiation increased 1 O2 formation in fructosazine and GlcN caramel. Bacillus subtilis was more resistant to UV-B as compared to E. coli strains tested. UV-B combined with fructosazine and GlcN caramel enhance antimicrobial efficacy. Fructosazine potentially forms endoperoxides upon UV-B irradiation. Abstract: This study investigated the effect of UV-B irradiation and the combinational effect with glucosamine caramel, fructosazine and riboflavin on the antimicrobial activities against Bacillus subtilis (ATCC 6633) and two strains of Escherichia coli ( AW 1.7 and ATCC 25922). The quantum yield of fructosazine was two times less than that of tryptophan, indicating its ability to emit fluorescent light but less efficiently than tryptophan. UV-B treatment alone was efficient to achieve a bactericidal effect for both E. coli stains tested, however no effect was found for Bacillus subtilis for up to 80 mJ/cm 2 UV-B. The combination of UV-B with photosensitizers fructosazine, glucosamine caramel and riboflavin enhanced the UV-B efficacy against E. coli strains at lower UV-B doses, while Bacillus subtilis ATCC 6633 was more resistant to the treatment combinations. High-performance liquid chromatography showed the production of different fructosazine reaction products occurred during irradiation, including the possible formation of endoperoxides.